COATING INCLUDING SILICA-BASED MATERIAL WITH PENDENT FUNCTIONAL GROUP - SALGUERO TINA T; STANFORD THOMAS B; ZINCK JENNIFER J (2008)
PROBLEM TO BE SOLVED: To provide a coating including a silica-based material having a plurality of pendent functional groups. SOLUTION: The coating comprises a silica-based material having a plurality of pendent functional groups, wherein at least one of the plurality of pendent functional groups preferably contains a urea group, more preferably a propyl urea group. The pendent functional group may comprise an ionic group or an ionizable group. Also disclosed is a method for producing a sol-gel coating comprising hydrolyzing at least one silica precursor containing the functional group to thereby polymerize the precursor. The coating film is provided on the surface of a bipolar plate of a fuel cell. COPYRIGHT: (C)2008,JPO&INPIT